STAT signaling in the pathogenesis and therapy of acute myeloid leukemia and myelodysplastic syndromes - Zoe King; Sudhamsh Reddy Desai; David A. Frank; Aditi Shastri (Neoplasia: An International Journal for Oncology Research)
Acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) represent complex hematopoietic malignancies characterized by ineffective hematopoiesis and dysregulated myeloid differentiation. Recent research has underscored the critical role of aberrant STAT signaling pathways, particularly involving STAT3 and STAT5, in the pathogenesis of these disorders. Aberrant activation of STAT proteins has been implicated as a mediator of oncogenesis in several malignancies. In this review, we discuss the role of STAT proteins in both regulated and dysregulated hematopoiesis, the consequences of dysregulation in acute myeloid leukemia and myelodysplastic syndromes, therapeutic strategies, and recent advancements in STAT-targeted therapy. By integrating findings from recent preclinical and clinical studies, this review provides insights into the evolving landscape of STAT-targeted therapies, highlighting the promise of these approaches in enhancing treatment efficacy and improving patient outcomes in high-risk hematologic malignancies.